The effects of intravenous tramadol vs. intravenous ketamine in the prevention of shivering during spinal anesthesia: A meta-analysis of randomized controlled trials - Fenta, Efrem; Kibret, Simegnew; Hunie, Metages; Tamire, Tadese; Fentie, Yewlsew; Seid, Shimelis; Teshome, Diriba (Frontiers in Medicine, 2022)
Background Shivering is a common complication after subarachnoid administration of local anesthetics. Intravenous ketamine and tramadol are widely available anti-shivering drugs, especially in developing settings. This meta-analysis aimed to compare the effects of intravenous ketamine vs. tramadol for post-spinal anesthesia shivering. Materials and methods PubMed/MEDLINE, Web of Science, Cochrane Library, Embase, and Google Scholar databases were used to search for relevant articles for this study. Mean difference (MD) with 95% confidence interval (CI) was used to analyze continuous outcomes, and risk ratio (RR) with 95% CI to analyze categorical results. The heterogeneity of the included studies was assessed using the I2 test. We utilized Review Manager 5.4.1 to perform statistical analysis. Results Thirteen studies involving 1,532 patients were included in this meta-analysis. Ketamine had comparable effects in preventing post-spinal anesthetics shivering [RR = 1.06; 95% CI (0.94, 1.20), P = 0.33, I2 = 77], and onset of shivering [MD = −0.10; 95%CI (– 2.68, 2.48), P = 0.94, I2 = 0%], lower incidences of nausea and vomiting [RR = 0.51; 95%CI (0.26, 0.99), P = 0.05, I2 = 67%], and lower incidences of bradycardia [RR = 0.16; 95%CI (0.05, 0.47), P = 0.001, I2 = 33%], higher incidence of hallucinations [RR = 12; 95%CI (1.58, 91.40), P = 0.02, I2 = 0%], and comparable effects regarding the incidences of hypotension [RR = 0.60; 95%CI (0.30, 1.21), P = 0.15, I2 = 54%] as compared to tramadol. Conclusions Intravenous ketamine and tramadol are comparable in the prevention of post-spinal anesthetic shivering. Ketamine had a better outcome with less occurrences of nausea, vomiting, and bradycardia. However, ketamine was associated with higher incidences of hallucinations than tramadol.